2017
DOI: 10.1371/journal.pone.0174546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitochondrially targeted carboxy proxyl nitroxide on Akt-mediated survival in Daudi cells: Significance of a dual mode of action

Abstract: Vicious cycles of mutations and reactive oxygen species (ROS) generation contribute to cancer progression. The use of antioxidants to inhibit ROS generation promotes cytostasis by affecting the mutation cycle and ROS-dependent survival signaling. However, cancer cells select mutations to elevate ROS albeit maintaining mitochondrial hyperpolarization (Δψm), even under hypoxia. From this perspective, the use of drugs that disrupt both ROS generation and Δψm is a viable anticancer strategy. Hence, we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In line with this scenario, scavenging mitochondrial O 2 •– through MitoTEMPO blunted the activation of AKT, reverted the Warburg effect and induced death in melanoma cells. 165 Moreover, Variar et al 166 observed that the mitochondria-targeted antioxidant Mito-CP enhances apoptotic cell death in a Burkitt’s lymphoma cell line by decreasing AKT activation and HIF-1α stabilisation under hypoxia, suggesting the possibility to block hypoxic adaptation in cancer cells by decreasing ROS generated by the ETC.…”
Section: Regulation Of Etc-mediated Ros Production By Oncogenesmentioning
confidence: 99%
“…In line with this scenario, scavenging mitochondrial O 2 •– through MitoTEMPO blunted the activation of AKT, reverted the Warburg effect and induced death in melanoma cells. 165 Moreover, Variar et al 166 observed that the mitochondria-targeted antioxidant Mito-CP enhances apoptotic cell death in a Burkitt’s lymphoma cell line by decreasing AKT activation and HIF-1α stabilisation under hypoxia, suggesting the possibility to block hypoxic adaptation in cancer cells by decreasing ROS generated by the ETC.…”
Section: Regulation Of Etc-mediated Ros Production By Oncogenesmentioning
confidence: 99%